(untitled) (Teresa Vigetti: Revista de Trabajo Social, 2025)
This paper presents a theoretical analysis and a brief description of the mental health field in Argentina. Interest in the topic arose after taking related courses and, particularly, from a practical experience within the training space of the Bachelor’s degree in Social Work program. This experience took place at the Psychosocial Rehabilitation and Community Integration Center "Asociación Civil Rumbos" in the city of Santa Fe. The main theoretical issues discussed relate to the difficulties in implementing the guidelines of National Mental Health Law No. 26.657/2010, specifically regarding the replacement of asylum-based institutions with community-based services. The paper concludes that the realities of the mental health field are too complex to be addressed by a single discipline or by a State that shows little interest in guaranteeing the right to mental health protection.